2017
DOI: 10.1186/s13045-017-0442-y
|View full text |Cite|
|
Sign up to set email alerts
|

A novel melittin nano-liposome exerted excellent anti-hepatocellular carcinoma efficacy with better biological safety

Abstract: Melittin is the main effective component of bee venom and has extensive biological functions; however, serious side effects have restricted its clinical application. Preclinical and clinical studies showed that the main adverse events were allergic reaction and pain at the administration site. To decrease the toxicity, we prepared melittin nano-liposomes by encapsulating melittin with poloxamer 188 and explored the inhibitory activities on liver cancer together with biological safety. Here, we showed that meli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…The encapsulation of melittin in Poloxamer 188 produces nanoliposome formulations that showed decreased inflammatory allergic reactions and toxicity in mice, while preserving anti-tumor activity such as growth suppression of subcutaneous and orthotopic hepatocarcinoma implants in mice. The anti-tumor activity of the new formulation is comparable to the FDA-approved sorafenib in hepatocarcinoma studies [ 75 , 76 ].…”
Section: Critical Issues Possible Solutions For Clinical Use Of Amentioning
confidence: 99%
“…The encapsulation of melittin in Poloxamer 188 produces nanoliposome formulations that showed decreased inflammatory allergic reactions and toxicity in mice, while preserving anti-tumor activity such as growth suppression of subcutaneous and orthotopic hepatocarcinoma implants in mice. The anti-tumor activity of the new formulation is comparable to the FDA-approved sorafenib in hepatocarcinoma studies [ 75 , 76 ].…”
Section: Critical Issues Possible Solutions For Clinical Use Of Amentioning
confidence: 99%
“…In another study the synergistic co-delivery of doxorubicin and Melittin using f nanoparticles for cancer treatment in LC-MS/MS indicated that the co-delivery system of Doxorubicin-Melittin loaded CA-MNPs is highly capable to be used in magnetically targeted cancer therapy [48]. Melittin nano-liposomes would have a better application in hepatocellular carcinoma cells (HCC) therapy due to induced apoptosis in hepatic carcinoma cells In-Vitro and vivo and inhibit hepatocellular carcinoma in LM-3 xenograft tumor model [49].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Melittin modified poloxamer liposomes were studied against hepatic carcinoma in a mice xenograft tumor model. This formulation showed increased safety and anti-hepatocarcinoma activity in vivo, inducing apoptosis of the cancerous hepatic cells [106]. Melittin liposomes showed antitumor activity similar to the FDA-approved anticancer drug sorafenibin, reducing hepatic tumor size.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…Melittin liposomes showed antitumor activity similar to the FDA-approved anticancer drug sorafenibin, reducing hepatic tumor size. Moreover, while naked melittin administration resulted in increased counts of neutrophils and eosinophils, indicating an inflammation and allergic reaction, melittin nano-liposomes effectively prevented anaphylaxis [106].…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%